Hormone replacement therapy after surgery for epithelial ovarian cancer - Saeaib, Nungrutai (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness and safety of hormone replacement therapy (HRT) in women treated surgically for epithelial ovarian cancer.